Bright and Early Books : Bears on Wheels - A Bright and Early Counting Book - Berenstain, Stan, 1923-; Berenstain, Jan, 1923- (New York, Random House, 1969)
An acrobatic act begins with one bear on a unicycle and ends with twenty-one bears and sixteen wheels flying through the air.
Keywords: Bears; Early readers